The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.expneurol.2020.113355
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of adult rat sensory and motor neuron axons through chimeric peroneal nerve grafts containing donor Schwann cells engineered to express different neurotrophic factors

Abstract: of adult rat sensory and motor neuron axons through chimeric peroneal nerve grafts containing donor Schwann cells engineered to express different neurotrophic factors,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…If the continuity of a damaged axon can be restored, the axon transport function can also be restored. The axon transport function is an important indicator reflecting the structure, metabolism, and functional integrity of a nerve, and the restoration of axon transport function after nerve injury repair is powerful evidence for nerve regeneration 34‐36 . In this study, the distal part of the transplanted nerve was infiltrated with FG, which can be transported to the body of the neuron by way of retrograde axoplasmic transport.…”
Section: Discussionmentioning
confidence: 93%
“…If the continuity of a damaged axon can be restored, the axon transport function can also be restored. The axon transport function is an important indicator reflecting the structure, metabolism, and functional integrity of a nerve, and the restoration of axon transport function after nerve injury repair is powerful evidence for nerve regeneration 34‐36 . In this study, the distal part of the transplanted nerve was infiltrated with FG, which can be transported to the body of the neuron by way of retrograde axoplasmic transport.…”
Section: Discussionmentioning
confidence: 93%
“…Axonal degeneration and demyelination are the critical pathological features of spinal cord injury, leading to permanent neurological defects (Novikova, Novikov, & Kellerth, 2000;Xie et al, 2016). There are increasing evidence that the transplantation of SCs provides a neuroprotective effect and promotes axonal regeneration and myelination in the CNS (Assinck et al, 2020;Godinho et al, 2020;Mousavi et al, 2019;Pearse et al, 2018;Wiliams & Bunge, 2012).Once SCs migrate at the lesion site after SCI, they break the myelin into small fragments and engulf them (Nagoshi et al, 2011), and remyelinate central axons (Bartus et al, 2016) and establish nodes of Ranvier on central axons to repair impulse conduction (Black, Waxman, & Smith, 2006). In contrast, myelin-forming oligodendrocytes in the CNS have little or no influence on the disposal of myelin (Kandel et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Following SCI, SCs in the nerve roots can migrate to the lesion site, myelinating regenerated or demyelinated axons in the injured spinal cord (Nagoshi et al, 2011). Numerous studies have demonstrated that SCs are prime candidates to promote axon growth and myelination, and SC transplantation is a promising therapeutic strategy for spinal cord repair (Assinck et al, 2020;Godinho et al, 2020;Mousavi et al, 2019;Pearse, Bastidas, Izabel, & Ghosh, 2018;Wiliams & Bunge, 2012).…”
mentioning
confidence: 99%
“…Chondroitin sulfate-A was detected using the monoclonal antibody clone 2H6, which recognizes multiple sequences containing CS-A units in CS chains ( Deepa et al, 2007 ) and binds effectively in immunohistochemistry ( Shimazaki et al, 2005 ). To label motoneurons, antibodies against choline acetyltransferase (ChAT) or NeuN that recognize α-motoneurons ( Friese et al, 2009 ; Godinho et al, 2020 ) were used. After the blocking procedure with Block Ace (5%, UK-B80, DS Pharma Biomedical Co., Ltd., Suita, Japan), the sections were incubated in a moist chamber overnight at 4°C with primary antibodies as follows: (1) a mixture of goat polyclonal antibody against ChAT (1:100, AB144P, Merck KGaA, Darmstadt, Germany) and mouse monoclonal IgM antibody against CS-A (10 μg/ml, Clone 2H6, NU-07-001, Cosmo Bio Co., Ltd., Tokyo, Japan); (2) a mixture of mouse monoclonal IgG antibody against NeuN (1:200, MAB377, Merck KGaA), mouse monoclonal IgM antibody against CS-A (10 μg/ml, Clone 2H6, NU-07-001, Cosmo Bio), and goat polyclonal antibody against 5-HT (1:2,000, PA1-18017, Invitrogen, Carlsbad, CA, United States); (3) a mixture of goat polyclonal antibody against 5-HT (1:2,000, PA1-18017, Invitrogen) and mouse monoclonal IgG antibody against GAP43 (1:100, ab129990, Abcam, Cambridge, United Kingdom); (4) a mixture of goat polyclonal antibody against ChAT (1:100, AB144P, Merck KGaA), mouse monoclonal antibody against synapsin I (1:200, VAM-SV009, Stressgen Biotechnologies Corp., San Diego, CA, United States), and rabbit polyclonal antibody against 5-HT (1:200, S-5545, Sigma-Aldrich, Merck KGaA); and (5) a mixture of rabbit polyclonal antibody against collagen IV (1:200, ab6586, Abcam), and mouse monoclonal IgM antibody against CS-A (10 μg/ml, Clone 2H6, NU-07-001, Cosmo Bio), diluted with 1% normal donkey serum, 0.2% bovine serum albumin, and 0.1% NaN 3 in 0.1 M PBST.…”
Section: Methodsmentioning
confidence: 99%
“…Chondroitin sulfate-A was detected using the monoclonal antibody clone 2H6, which recognizes multiple sequences containing CS-A units in CS chains (Deepa et al, 2007) and binds effectively in immunohistochemistry (Shimazaki et al, 2005). To label motoneurons, antibodies against choline acetyltransferase (ChAT) or NeuN that recognize α-motoneurons (Friese et al, 2009;Godinho et al, 2020) were used. After the blocking procedure with Block Ace (5%, UK-B80, DS Pharma Biomedical Co., Ltd., Suita, Japan), the sections were incubated in a moist chamber overnight at 4 • C with primary antibodies as follows: (1) a mixture of goat polyclonal antibody against ChAT (1:100, AB144P, Merck KGaA, Darmstadt, Germany) and mouse monoclonal IgM antibody against CS-A (10 µg/ml, Clone 2H6, NU-07-001, Cosmo Bio Co., Ltd., Tokyo, Japan);…”
Section: Immunohistochemistrymentioning
confidence: 99%